Invisible World : the digestive system (New Delhi : Sterling Press.)
1. Gastrointestinal system--Physiology--Juvenile literature. 2. Digestive organs--Physiology--Juvenile literature. 3. Digestive system. 4. The Invisible world.
Basic ed. students